The Correlation Between the Number of Hours Spent on Reading and Language Competence Gained? - Bahrani, Taher (Richtmann Publishing, 2011)
In academia, there is a sort of hidden argument about the factors which shape effective reading and the amount of languagecompetence gained through reading. In this regard, few believe that the number of the hours spent daily on reading different sources willlead to effective reading and high language competence regardless of the fact that how this amount of time is spent. On the contrary, somebelieve that the number of hours has nothing to do with effective reading and this time measurement criterion has no validity in relation toeffective reading and the development of specialized language competence. Accordingly, the present paper tried to consider the essentialfactors which lead to effective reading and the development of specialized competence. Moreover, it aimed at providing evidence of the factthat high specialized language competence is basically the result of effective reading rather than the number of hours spent on readingsomething.